2005
DOI: 10.1530/eje.1.02035
|View full text |Cite
|
Sign up to set email alerts
|

Sex-specific association of PTPN22 1858T with type 1 diabetes but not with Hashimoto’s thyroiditis or Addison’s disease in the German population

Abstract: Background: Endocrine autoimmune disorders share genetic susceptibility loci, causing a disordered T-cell activation and homeostasis (HLA class II genes, CTLA-4). Recent studies showed a genetic variation within the PTPN22 gene to be an additional risk factor. Materials and Methods: Patients with type 1 diabetes (n ¼ 220), Hashimoto's thyroiditis (n ¼ 94), Addison's disease (n ¼ 121) and healthy controls (n ¼ 239) were genotyped for the gene polymorphism PTPN22 1858 C/T. Results: Our study confirms a significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
56
3
8

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(77 citation statements)
references
References 29 publications
10
56
3
8
Order By: Relevance
“…Our results are consistent with the finding observed in Dutch population [22] and not consistent with findings obtained in Ukrainian [23] and German [24] population.…”
supporting
confidence: 79%
“…Our results are consistent with the finding observed in Dutch population [22] and not consistent with findings obtained in Ukrainian [23] and German [24] population.…”
supporting
confidence: 79%
“…Three showed a significant association, whereas the other three studies showed a tendency toward a positive association but failed to reach the significance threshold. 25,87,109,110 Meta-analysis showed a significant association between the T allele and Addison's disease (OR ¼ 1.43; 95% CI ¼ 1.21-1.68, P ¼ 2.36 Â 10 À 5 ) (Figure 2e). Anti-neutrophil cytoplasmic antibody (ANCA)-associated vasculitis includes Wegener's granulomatosis, microscopic polyangiitis and Churg-Strauss syndrome.…”
mentioning
confidence: 98%
“…The association of PTPN22 1858C/T polymorphism with HT is much weaker than the association with GD (Kahles et al, 2005). T-allele carriers were reported to be at particularly high risk of developing HT (Dultz et al, 2009).…”
Section: Ptpn22 Genementioning
confidence: 88%